2017
DOI: 10.1086/691147
|View full text |Cite
|
Sign up to set email alerts
|

Mn-Fe-Enhancing Budding Bacteria in Century-Old Rock Varnish, Erie Barge Canal, New York

Abstract: Fossil remnants of bacteria involved in the enhancement of manganese and iron rarely occur within the microstratigraphy of rock varnishes collected from warm desert environments, because varnish formation processes ultimately destroy these microfossils through remobilization of Mn-Fe and reprecipitation in a clay-mineral matrix. In contrast, Mn-Fe encrustations on budding bacteria commonly occur within varnishes that formed within just a century along the Erie Barge Canal, New York. Nanoscale imagery and eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 94 publications
(143 reference statements)
3
24
0
Order By: Relevance
“…The Mn-rich casts observed in association with fossilized budding bacteria display a fibrous texture of fine spines and long bundles of hair-like manganese oxides very similar to what has been seen on the cell wall of natural microbial communities [124], culturing studies [125], and fossilized budding bacteria in varnishes non-cold-climate settings [126]. These fibrous forms could be the result of different processes, such as Mn(II) absorption [127], bacterial oxidation [126], bacterial use of Mn (IV) as extracellular respiratory electron acceptors [128], or some combination of processes.…”
Section: Nanoscale Observations Of Rock Coatingsmentioning
confidence: 58%
“…The Mn-rich casts observed in association with fossilized budding bacteria display a fibrous texture of fine spines and long bundles of hair-like manganese oxides very similar to what has been seen on the cell wall of natural microbial communities [124], culturing studies [125], and fossilized budding bacteria in varnishes non-cold-climate settings [126]. These fibrous forms could be the result of different processes, such as Mn(II) absorption [127], bacterial oxidation [126], bacterial use of Mn (IV) as extracellular respiratory electron acceptors [128], or some combination of processes.…”
Section: Nanoscale Observations Of Rock Coatingsmentioning
confidence: 58%
“…Some authors have suggested that abiotic processes are sufficient to explain the Mn oxidation and deposition (Collins and Buol, 1970;Elvidge and Iverson, 1983;Goldsmith et al, 2014;Perry et al, 2005;Thiagarajan and Lee, 2004). On the contrary, there is a large body of evidence that suggests an involvement of microorganisms (bacteria or fungi) in the oxidation and precipitation of Mn (Dorn et al, 2013;Gadd, 2017;Jones, 1991;Krinsley et al, 2012Krinsley et al, , 2017Krumbein and Jens, 1981;Kuhlman et al, 2006Kuhlman et al, , 2008Laudermilk, 1931;Marnocha and Dixon, 2013;Wang et al, 2011). The lack of microfossils (Macholdt et al, 2015(Macholdt et al, , 2017b and of evidence for the presence of activated Mnoxidizing enzymes in varnish (Lang-Yona et al, 2018) does not rule out a bacterial role in Mn precipitation, considering the length of time involved in its formation (Dorn and Krinsley, 2011;Krinsley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Using objective data in warm deserts, the vertical rate of varnish accumulation is in the order of micrometers per thousand years (Dorn, 1998; Liu and Broecker, 2000). In more mesic microenvironments, even in a desert, rates can accelerate to micrometers per century (Spilde et al, 2013), with varnishing in humid settings reaching micrometers per decade (Krinsley et al, 2017). All of these studies, however, focus on varnish that ‘started from scratch’ on a bedrock surface and not on a pre-existing rock coating.…”
Section: Discussionmentioning
confidence: 99%